Pemberdayaan dan Strategi Marketing Petani Lebah Madu - Selfi Aprillia Ningrum; Jevita Rizqiani; Putri Sabila Cahyani; Puspita Jati Dwi Ningsih; Zahroil Laila; Fitri Yulianti (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Kutosari Village is known for its honey, as many of its residents are honey farmers. However, honey farmers in Kutosari Village face various challenges in marketing their products. This is due to the way of selling honey that only sells bottled products without any other innovations. The purpose of this empowerment is to increase honey sales of Kutosari village honey farmers through appropriate marketing strategies. This empowerment method begins with problem identification, preparation, implementation, monitoring and evaluation. The results of this activity are making honey processed innovations such as honey candy, probiotic honey syrup and honey jam, selling bee food source seeds, making attractive packaging such as honey bouquet, honey hampers and more creative honey stickers, using and managing social media attractively and creatively. With the implementation of the program by the PPK Ormawa KSR team, it is hoped that by improving effective marketing strategies, honey bee farmers in Kutosari Village can increase their income and introduce more innovative honey products from their village to a wider market.